Kajian Pengembangan Enterprise Architecture Pada Industri Software House - Saiful Azhari Muhammad; Richardus Eko Indrajit; Erick Dazki (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2022)
The presence of a local software house company is a solution choice for companies on a small, medium and large scale. The software house company has been able to provide solutions to fulfill information systems and produce good quality software products. However, local software house companies face operational problems with the company's internal information technology in completing projects obtained from their customers. To solve the company's internal information technology problems, the company applies the enterprise architecture method to streamline the company's operations. So far, information technology operations in software house companies have experienced ineffective operations with various application systems that have been implemented. Changes in information technology operations by rearranging using the Enterprise Architecture method, and applying it to the company's software house. This study aims to develop Enterprise Architecture in a software house company, where all are designed using Information Technology Planning based on the TOGAF-based Enterprise Architecture Framework. With the application of Enterprise Architecture, information technology operations can be changed to be more organized and more efficient in supporting company operations.Keyword: Software House; Enterprise Architecture; TOGAF; Information System Abstrak. Hadirnya perusahaan software house lokal menjadi pilihan solusi bagi perusahaan dalam skala kecil, skala medium dan skala besar. Perusahaan software house telah mampu memberikan solusi pemenuhan sistem informasi dan menghasilkan produk software yang berkualitas baik. Namun perusahaan software house lokal menghadapi permasalahan operasional informasi teknologi internal perusahaan dalam menyelesaikan proyek yang didapat dari pelanggannya. Untuk menyelesaikan permasalahan informasi teknologi internal perusahaan, perusahaan menerapkan metode enterprise arsitektur dalam mengefektifkan operasionalnya. Selama ini operasional teknologi informasi di perusahaan software house mengalami operasional yang tidak efektif dengan berbagai sistem aplikasi yang telah diterapkan. Perubahan operasional teknologi informasi dengan menata ulang menggunakan metode Enterprise Architecture, dan menerapkannya ke dalam perusahaan software house. Penelitian ini bertujuan untuk mengembangkan Enterprise Architecture pada perusahaan software house, dimana semua dirancang dengan menggunakan Information Technology Planning dengan Framework Enterprise Architeture berbasis TOGAF. Dengan penerapan Enterprise Architecture dapat mengubah operasional informasi teknologi menjadi lebih tertata dan lebih efisien dalam mendukung operasional perusahaan.Kata kunci: Software House; Enterprise Architecture; TOGAF; Sistem Informasi